The life and literary works of Peter Tshobiso Mtuze: a critical analysis - Mafrika, Andile Ernest (Rhodes University, Faculty of Humanities, School of Languages, 2017)
This thesis is an exploration of the concept of Mphahlele's African Humanism, against the backdrop of the life and work of Peter Tshobiso Mtuze, well-known author of isiXhosa books, critic, academic and spiritual leader. Mtuze's commitment to the collective rather than the individual is clearly illustrated in the thesis, suggesting that his early life of struggle, his belated development as an acclaimed academic, as well as his spiritual growth are all intertwined and underpinned by African Humanism and an Afrocentric ethos.The thesis consists of six chapters with each chapter focusing on a particular aspect of the research topic. Chapter One deals with the introduction to the research topic. Part of the introductory material consists of conventional preliminaries such as a research statement, aim of study, methodology, main assumptions of the study and the significance and benefit of the study. Chapter Two is the theoretical foundation of the thesis. It covers the origin of African Humanism as consciousness and as a system of society, oral and written literature in Africa and the early Xhosa literary humanism. Chapter Three is an overview of the biographical background of Peter Tshobiso Mtuze, his Pass Law battles in different towns of South Africa, how he joined the African National Congress (ANC) and his working life and writing life. Chapter Four analyses two major novels, UDingezweni and Alitshoni lingaphumi, and a short story book, Amathol' eendaba. The analysis aims at revealing African consciousness and African way of life with specific reference to Xhosa people. Chapter Five deals with Xhosa spirituality, its aspects and symbols, Mtuze's Spirituality and Anglicanism and his writings. Chapter Six is a general conclusion that highlights the main aspects of the thesis, the African personality and the prospects of African humanism in today's world.
Keywords: Mtuze, P T -- Criticism and interpretation; Mtuze, P T -- UDingezweni; Mtuze, P T -- Alitshoni lingaphumi; Mtuze, P T -- Amathol' eendaba.; Authors, Xhosa; Xhosa literature -- History and criticism